An exploratory analysis of the definition and conceptualization of cultural landscape - Amanda Rosetia; Nor Zalina Harun (Penerbit Universiti Kebangsaan Malaysia, 2023)
Many have analyzed “cultural landscape” and its meaning. Some recall the basics of diverse fields, such as “a cultural landscape is a landscape that has been cultivated” or “culture that dwells in a landscape.” The need to decipher “cultural landscape” has driven research on people’s cultural views of their immediate surroundings. This study suggests cultural landscape research in South East Asia against the backdrop of emerging approaches in cultural landscape research worldwide. Thus, this essay will examine cultural dynamics arguments and hypotheses. This exploratory review and inductive qualitative analysis examined “cultural landscape” studies from the early 19th century to the present. Google Scholar, Science Direct, and other professional education search portals were used to find and examine over fifty papers on local cultural landscapes. To understand cultural landscape studies’ interconnectedness, research results are synthesized and thematized. Therefore, the study provides a concise overview of eight (8) significant fields of study: geography, governance, environmental studies, etymology, tourism, agricultural studies, health studies, and technology. Only tourism, ecology, geography, and politics study Indonesia’s cultural landscape. However, despite the abundance of creative and literary creation in Indonesia, little progress has been made in this area. Instead, new findings in domains as diverse as literature, semantics, and etymology are advancing our knowledge of the cultural environment and its effects.